STUDI KOMPARASI BEBERAPA FAKTOR RISIKO KEJADIAN TUBERKULOSIS PARU BTA POSITIF DI DAERAH PANTAI DAN DAERAH PEGUNUNGAN - Teguh Dhika; Dwi Sarwani Sri Rejeki (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT Lung Tuberculosis Disease (Lung TB) is still become public health problem in Indonesia mainly in Central Java Province. Lung TB cases on Central Java is including high, among other things in Cilacap Regency and Banyumas Regency. Area of Health Center of Binangun (Cilacap Regency) including coastal area and area of Health Center of II Sumbang (Banyumas Regency) including mountain area. Both of them have high case detection rate of BTA positive lung TB in 2007 (>70%) whereas have different geographic characteristic. Aim of this research was to compare several risk factors of lung TB incidence (house physical condition and behavior of lung TB patient) in coastal area and mountain area. It was an comparison study with cross sectional approach. The number of samples was 35 lung TB patients in coastal area (Health Center of Binangun) and 31 lung TB in mountain area (Health Center of II Sumbang), and it was taken with simple random sampling. The data was analyzed with univariate and bivariate analysis by using test of T-test Two Independent, Mann-Whitney and Chi-Square Test. The research result showed that house physical condition and behavior of lung TB patient in coastal area and mountain area, majority have not fulfill heatlh requirement. In addition, based on statistical test showed that there is difference of illumination (p = 0,002), house humidity (p=0,002) sleep behavior (p = 0,000), and also behavior to open bedroom window of lung TB patient (p = 0,000) in coastal area and mountain area. Based on that research, suggested for public especially lung TB patient in coastal area and mountain area in building house must considering health house requirement and also have health life behavior. Keywords : area, pantai, pegunungan, Tb Paru, faktor risiko Kesmasindo. Volume 4(2), Juli 2011, hlm. 184-192